An adaptive prototype design to maximize power harvesting using electrostrictive polymers - Meddad, M.; Eddiai, A.; Guyomar, D.; Belkhiat, S.; Cherif, A.; Yuse, K.; Hajjaji, A. (Journal of applied physics, 2012)
The harvesting energy with electrostrictive polymers has great potential for remote applications such as invivo sensors, embedded micro-electro-mechanical systems devices, and distributed network instruments. A majority of current research activities in this field refers to classical piezoelectric ceramics, but electrostrictive polymers offer promise of energy harvesting with few moving parts; power can be produced by simply stretching and contracting a relatively low-cost rubbery material. The use of such polymers for energy harvesting is a growing field, which has great potential from an energy density viewpoint. The output power is inversely proportional to the harvester's frequency bandwidth. Consequently, it is much harder to efficiently harvest power from low-frequency sources with a large frequency band response and with a very small system size than from a stabilized high-frequency vibration source. This paper presents a new structure that is able to predict mechanical frequency excitation in order to increase power-harvesting capabilities of electrostrictive polymers. An equivalent structure scheme has been developed by using current and electrical schemes models. With a transverse strain of 0.5% and a bias field of 10 V/μm, such a process rendered it possible to increase the converted power by 80% with a low-frequency mechanical excitation. This study contributes to provide a framework for developing an innovative energy-harvesting technology that collects vibrations from the environment and converts them into electricity to power a variety of sensors.